1997
DOI: 10.1037/0278-7393.23.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thematic relations on the comprehension of modifier–noun combinations.

Abstract: To comprehend a nonpredicating combination involving a modifier (e.g., mountain) and a head noun (e.g., stream), one must specify a thematic relation (e.g., a stream in the mountains) that links the 2 constituent concepts. The authors investigated the influence of thematic relations on the comprehension of nonpredicating combinations. Experiments 1 and 3 demonstrated that people use information about what relations the constituents typically instantiate during conceptual combination. More specifically, a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

49
575
10
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 264 publications
(639 citation statements)
references
References 42 publications
49
575
10
5
Order By: Relevance
“…The RICE (Relational Interpretation Competitive Evaluation; Spalding et al, 2010) theory of compound interpretation is a development and extension of the CARIN (Competition Among Relations In Nominals; Gagné & Shoben, 1997) theory. According to RICE, the interpretation of a compound is arrived at through a suggestevaluate-elaborate process.…”
Section: Extending Theories Of Novel Compound Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…The RICE (Relational Interpretation Competitive Evaluation; Spalding et al, 2010) theory of compound interpretation is a development and extension of the CARIN (Competition Among Relations In Nominals; Gagné & Shoben, 1997) theory. According to RICE, the interpretation of a compound is arrived at through a suggestevaluate-elaborate process.…”
Section: Extending Theories Of Novel Compound Processingmentioning
confidence: 99%
“…Finally, once a suggested relation has been selected and evaluated as appropriate, there is an elaboration stage in which the full meaning of the compound is developed. Gagné and Shoben (1997) showed that the ease of interpretation of novel compounds depended on the relative frequency with which the required relation had previously been used with the modifier. Recently, Spalding and Gagné (2008) showed that the main determinate of ease of interpretation across items in the Gagné and Shoben (1997) data was the number of "strong but wrong" relations for the modifier.…”
Section: Extending Theories Of Novel Compound Processingmentioning
confidence: 99%
See 3 more Smart Citations